The colonial landscape of the British Caribbean - Leech, Roger; Leech, Pamela (Society for Post-Medieval Archaeology monograph, 2021)
"This volume brings together new research on the archaeology of the colonial landscape of the Caribbean. It focusses on the seventeenth and eighteenth centuries and on the British Caribbean: notably Bermuda, Jamaica, Florida, Barbados, Antigua, and especially St. Kitts and Nevis. Chapters cover a wide range of landscapes -- domestic, military and industrial -- and interests, including the archaeology and architecture of African-Caribbean slavery and emancipation, European settlements, sugar production, burial grounds, cartography, fortifications and trade."--